(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Ludwig Mies van der Rohe is regarded as one of the pioneers of modernist architecture. Rohe’s works in both architecture and products showed his own characteristics and these characteristics appeared repeatedly in different works. His design is simple and exquisite, and gradually formed Rohe’s design vocabulary and style. The design of his works concise and refined, both elegant and popular. This research uses Form Synth style analysis to analyze Rohe’s style characteristics and shaping rules, and integrates them in a form of construction. It summarizes the design process of Rohe’s design style reproduction, and verifies the feasibility of form construction and redesigns the new products of Rohe’s style. Products, hope to provide Rohe’s design experience, so that Rohe’s design style can be continued. It is more verified that the form construction method can be reproduced.